The First Saint Petersburg Regional Inflammatory Bowel Diseases Registry on the Basis of the Regional Health Information System: Principles of Functioning, Testing Results, Plan of Development - Yu. P. Uspenskiy; A. M. Sarana; L. N. Melentyeva; A. V. Yazenok; S. V. Petrov; Yu. A. Fominykh; S. V. Ivanov; A. V. Shotik; A. M. Segal; T. V. Gorbacheva; S. D. Plotnikova; K. V. Dronov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present the principles of functioning of the regional registry of inflammatory bowel disease (IBD) patients in Saint Petersburg on the basis of the City Health Information System (Saint Petersburg IBD Registry).Key points. The Saint Petersburg IBD Registry consists of General Statistical Module and Clinical Module. The General Statistical Module is intended to analyze the prevalence of ulcerative colitis and Crohn's disease, the number of patient visits to medical institutions; to assess the burden on the healthcare system, demographic characteristics, routing and mortality for the whole region. The Clinical Module allows to assess the IBD features in prospective observation. The register case report form is integrated into the patient's status in the Medical Information System of the medical institution. Saint Petersburg IBD Registry operates on the basis of the Saint Petersburg Medical Center of Information and Analysis within the framework of the Regional Medical Data Collection System of the Russian state information system “Regional Fragment of the Unified State Information System in the Healthcare Branch”. The accumulation of prospective data in the Clinical Module continues, which in the near future will make it possible to test and configure the automated analytical block of the registry.Conclusion. The functioning of the Saint Petersburg IBD Registry allows to achieve following primary goals within region: assessment of the epidemiological features of IBD in Saint Petersburg; dynamic assessment of the disease features; assessment and planning of health care resources required to provide care to IBD patients; improvement of approaches to the treatment taking into account the specifics of the region; assessment of the effectiveness and tolerability of specific treatment including biologics.